Optimization of Heat Sector Decarbonization Strategy through Coordinated Operation with Electricity System. (December 2017) - Zhang, X.; Strbac, G.; Djapic, P.; Teng, F.
Abstract: Heat networks (HNs) and heat pumps (HPs) are potential low-carbon heating technologies that can deliver the 2050 carbon target reduction in the UK. The optimal design of the heating system on a national scale to maximize the economic benefits while satisfying carbon target remains an open question. By applying the HN investment model and the integrated heat and electricity system model, this paper compares the decomposed system cost of HNs, hybrid HP-Bs (HPs and gas boilers) and air source HPs (ASHP), analyzes the impact of different heating strategies on the operation and investment of the electricity system, and presents the optimized strategy for heat sector decarbonization. According to the cost assumption, hybrid HP-Bs based approach may have significant economic advantage over the other two heating technologies when each of these is applied individually, while HNs in urban areas play an important role in the optimized heat technology portfolio.